ACE inhibitor in complex therapy of functional class II-III chronic heart failure in patients with chronic obstructive pulmonary disease - A. G. Evdokimova; A. E. Radzevich; N. O. Kuvyrdina; O. I. Tereshchenko; E. V. Kovalenko; N. V. Churkina; T. A. Komissarova; V. V. Evdokimov; N. I. Shakhova (Российский кардиологический журнал, 2005)
.